The species of the genus Triraphis Ruthe, 1855 (Hymenoptera: Braconidae: Rogadinae) in the fauna of the Korean Peninsula - Belokobylskij, Sergey A.; Ku, Deok-Seo (Zootaxa, 2025)
The species of the rogadine genus Triraphis Ruthe in the fauna of the Korean Peninsula is reviewed. A new species Triraphis storozhenkoi Belokobylskij & Ku, sp. nov. is described and illustrated. The species Triraphis brevis Chen & He, 1997, T. flavus Chen & He, 1997, and T. terebrans Chen & He, 1997 are recorded in the fauna of peninsula for the first time. An illustrated key for the six species known from Korea is provided.